2010
DOI: 10.1038/ng.704
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation at Strubbelig Receptor Kinase 3 drives immune-triggered incompatibilities between Arabidopsis thaliana accessions

Abstract: Accumulation of genetic incompatibilities within species can lead to reproductive isolation and, potentially, speciation. In this study, we show that allelic variation at SRF3 (Strubbelig Receptor Family 3), encoding a receptor-like kinase, conditions the occurrence of incompatibility between Arabidopsis thaliana accessions. The geographical distribution of SRF3 alleles reveals that allelic forms causing epistatic incompatibility with a Landsberg erecta allele at the RPP1 resistance locus are present in A. tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
129
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(138 citation statements)
references
References 34 publications
7
129
2
Order By: Relevance
“…Finally, the pseudooverdominance hypothesis also explains heterosis with the complementation of recessive alleles but proposes that when linked in repulsion, such alleles appear overdominant. Outside of these classical hypotheses, some cases of hybrid inferiority (19)(20)(21)(22) and hybrid superiority (23-30) have been linked to epistatic interactions between parental alleles.The availability of completely homozygous natural accessions has made the model plant Arabidopsis thaliana an excellent subject for studies of natural variation. Collections of sequenced accessions enable replicated genome-wide association (GWA)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the pseudooverdominance hypothesis also explains heterosis with the complementation of recessive alleles but proposes that when linked in repulsion, such alleles appear overdominant. Outside of these classical hypotheses, some cases of hybrid inferiority (19)(20)(21)(22) and hybrid superiority (23-30) have been linked to epistatic interactions between parental alleles.The availability of completely homozygous natural accessions has made the model plant Arabidopsis thaliana an excellent subject for studies of natural variation. Collections of sequenced accessions enable replicated genome-wide association (GWA)…”
mentioning
confidence: 99%
“…Finally, the pseudooverdominance hypothesis also explains heterosis with the complementation of recessive alleles but proposes that when linked in repulsion, such alleles appear overdominant. Outside of these classical hypotheses, some cases of hybrid inferiority (19)(20)(21)(22) and hybrid superiority (23)(24)(25)(26)(27)(28)(29)(30) have been linked to epistatic interactions between parental alleles.…”
mentioning
confidence: 99%
“…tauschii. Disease resistance genes encoding NB-LRR-type resistance (R) proteins and R-interacting proteins have been identified as causal genes for hybrid incompatibilities such as hybrid necrosis in higher plants Alcázar et al, 2009Alcázar et al, , 2010Yamamoto et al, 2010;Chen et al, 2013). Among the 33 Ae.…”
Section: Resultsmentioning
confidence: 99%
“…Another Hch gene, Hch2, complementary to Hch1 is proposed to be present in the AB genome of tetraploid wheat, but no information on it or its chromosome location has been reported. In hybrid necrosis of higher plants, most causal genes that have been isolated to date are related to disease resistance Alcázar et al, 2009Alcázar et al, , 2010Yamamoto et al, 2010). In our previous study, comparative transcriptome analyses showed that up-regulation of defense-and carbohydrate metabolism-related genes is common in hybrid chlorosis and type III necrosis, suggesting the existence of common mechanisms that induce their symptoms (Nakano et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports showed that the causal genes for hybrid necrosis are defense response-related genes in higher plants such as Arabidopsis and lettuce. [13][14][15][16] These hybrid necrosis genes act to accelerate genetic differentiation among genetically related accessions in the same species and between hybrid necrosis sometimes appears in triploid hybrids between tetraploid wheat and Aegilops tauschii Coss. two types of hybrid necrosis (type ii and type iii) were observed when cultivar Langdon was used as female parent for hybrid production.…”
mentioning
confidence: 99%